2013
DOI: 10.1016/j.hlc.2013.05.420
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Oral Ivabradine Versus Beta-blocker in Achieving Heart Rate Reduction Pre-Computed Tomography Coronary Angiogram (CTCA)

Abstract: Background: Pulmonary vein stenosis or thrombosis (PVST) following lung transplantation is a rare but serious complication that may lead to graft failure. Diagnosis is challenging, as its radiographical features mimic infection or other causes of pulmonary oedema. Transoesophageal echocardiography is often requested to evaluate anastamoses to exclude PVST, though reference ranges for normal Doppler flow in this setting are not widely known, and pulmonary vein velocities are often elevated in the immediate post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Although β‐blockers are generally used to achieve short‐term HR reduction during the scan, 16 studies have also investigated ivabradine for this purpose (Table 4). 68–83 One study did not show a benefit of adding single‐dose ivabradine to bisoprolol for additional HR lowering, whereas three studies demonstrated similar HR reduction compared to β‐blockers 70,74,81,82 . One of these studies reported more than twice as many patients treated with ivabradine required additional β‐blockade compared to metoprolol‐treated patients 82 .…”
Section: Resultsmentioning
confidence: 99%
“…Although β‐blockers are generally used to achieve short‐term HR reduction during the scan, 16 studies have also investigated ivabradine for this purpose (Table 4). 68–83 One study did not show a benefit of adding single‐dose ivabradine to bisoprolol for additional HR lowering, whereas three studies demonstrated similar HR reduction compared to β‐blockers 70,74,81,82 . One of these studies reported more than twice as many patients treated with ivabradine required additional β‐blockade compared to metoprolol‐treated patients 82 .…”
Section: Resultsmentioning
confidence: 99%
“…Ivabradine is undoubtedly a potentially attractive alternative for inappropriate sinus tachycardia, stable angina, heart failure, and other cardiovascular diseases, and it has good prospects for clinical application. A number of studies [1,2,3,4,5,6,7,8,9,10] have shown that ivabradine plays an important role in HR reduction in CTCA, particularly in terms of quantification of the efficacy of pretreatment with ivabradine before CTCA. We therefore examined whether there was a significant difference via meta-analysis.…”
Section: Introductionmentioning
confidence: 99%